Beyond the Lungs: A Rare Case of Extrapulmonary Tuberculosis Presenting With Neck Vein Thrombosis and Seizure - Hamda Al-Mansoori; M. Z. Sharaf Eldean; Abdelkareem Alhyari; Mahmoud Tabouni (Case Reports in Infectious Diseases)
Conclusion: Clinicians should maintain a high index of suspicion for extrapulmonary TB in atypical thrombotic events. Early tissue diagnosis and a multidisciplinary approach are key to effective management and favorable outcomes.